Congenital sideroblastic anaemia - Kavya Sree Velchuri; Mallikarjuna Shetty; Adiraju Krishna Prasad; Purna Surya Kiran Pentakota (Journal of Clinical and Scientific Research)
A 24-year-old male born out of a consanguineous marriage presented with a long-standing history of microcytic anaemia. He was treated elsewhere for the same with haematinics and packed red cell transfusions and had not shown improvement. Mild pallor and splenomegaly were noted on examination. After excluding other causes of microcytic anaemias bone marrow study was done. It revealed megaloblastoid erythropoiesis and ring sideroblasts. Genetic analysis showed a known homozygotic mutation in the solute carrier family 25 member 38 (SLC25A38) gene that causes autosomal recessive sideroblastic anaemia (SBA).